2015
DOI: 10.1103/physrevd.92.104038
|View full text |Cite
|
Sign up to set email alerts
|

Towards realisticf(T)models with nonminimal torsion-matter coupling extension

Abstract: Using the observation data of SNeIa, CMB and BAO, we establish two concrete f (T ) models with nonminimal torsion-matter coupling extension. We study in detail the cosmological implication of our models and find they are successful in describing the observation of the Universe, its large scale structure and evolution. In other words, these models do not change the successful aspects of ΛCDM scenario under the error band of fitting values as describing the evolution history of the Universe including radiation-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 57 publications
0
43
0
Order By: Relevance
“…[31], in cosmological cases, i.e. with the Friedmann-Lemaître-Robertson-Walker (FLRW) metric g μν = diag(1, −a, −a, −a), Eq.…”
Section: Brief Review Of the Theorymentioning
confidence: 99%
See 2 more Smart Citations
“…[31], in cosmological cases, i.e. with the Friedmann-Lemaître-Robertson-Walker (FLRW) metric g μν = diag(1, −a, −a, −a), Eq.…”
Section: Brief Review Of the Theorymentioning
confidence: 99%
“…As a further extension, and an analogy to that of f (R) theories [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29], non-minimal torsion-matter coupling f (T ) gravity has been proposed and studied [30]. In the previous research [31], using the observation data of type Ia supernovae (SNeIa), cosmic microwave background (CMB), and baryon acoustic oscillations (BAO), we established two concrete f (T ) models with non-minimal torsion-matter coupling extension, and we found that they are successful in describing the observation of the Universe and its large-scale structure and evolution. The joint fitting led to m0 = 0.255 ± 0.010, b0 h 2 = 0.0221 ± 0.0003 and H 0 = 68.54 ± 1.27 for model I and m0 = 0.306 ± 0.010, b0 h 2 = 0.0225±0.0003 and H 0 = 60.97±0.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Lagrangian of TEGR, the torsion scalar T by contractions of the torsion tensor takes the place of curvature scalar R. The simplest approach in TEGR to modify gravity is f (T ) theory [24,25], whose important advantage is that the field equations are second order but not fourth order as in f (R) theory. Recently, we established two concrete f (T ) models which do not change the successful aspects of the ΛCDM scenario under the error band of fitting values as describing the evolution history of the universe including the radiation-dominated era, the matterdominated era and the present accelerating expansion [26]. We also considered the spherical collapse and virialization in f (T ) gravities [27].…”
Section: Introductionmentioning
confidence: 99%
“…They discussed this theory as regards cosmological aspects of an evolving universe and deduced that the universe may represent quintessence, phantom or crossing of phantom-divide line, inflationary era, de Sitter accelerating phase, in short, one has a unified description. In this version of gravity, Nashed [60], Feng et al [61], and Carloni et al [62] studied spherically symmetric solutions, cosmological evolutions, and they compared their results with observational data and phase space analysis, respectively. Garcia and Lobo [63] explored wormhole solutions by a non-minimal curvaturematter coupling taking linear functions, f 1 = R, f 2 = R. They concluded that the wormhole solutions in a realistic manner depend on higher values of the coupling parameter.…”
Section: Introductionmentioning
confidence: 99%